2015
DOI: 10.3390/app5041323
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Continuous-Wave Directly-Diode-Pumped Fiber Raman Lasers

Abstract: We describe novel fiber Raman lasers pumped directly by spectrally combined high power multimode laser diodes at ∼975 nm and emitting at ∼1019 nm. With a commercial multimode graded-index fiber, we reached 20 W of laser output power with a record slope efficiency of 80%. With an in-house double-clad fiber, the beam quality improved to M 2 = 1.9, albeit with lower output power and slope efficiency due to higher fiber loss. We believe this is the first publication of a fiber Raman laser cladding-pumped directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 21 publications
(23 reference statements)
0
38
1
Order By: Relevance
“…This overcame the gain saturation, and resulted in compression of the pulse duration. Besides, in our experiment for the nonlinear LMA fiber, group velocity dispersion (GVD) in high-order modes could compensate for material group velocity mismatch, when fundamental and parametric waves were propagating with different modes [10,20]. Thus, efficient nonlinear parametric amplification was achieved.…”
Section: As Depicted Inmentioning
confidence: 99%
“…This overcame the gain saturation, and resulted in compression of the pulse duration. Besides, in our experiment for the nonlinear LMA fiber, group velocity dispersion (GVD) in high-order modes could compensate for material group velocity mismatch, when fundamental and parametric waves were propagating with different modes [10,20]. Thus, efficient nonlinear parametric amplification was achieved.…”
Section: As Depicted Inmentioning
confidence: 99%
“…First direction continues the study initiated in Ref. [5] with a focus on the opportunities of high-quality beam generation using fiber Bragg gratings (FBGs) as cavity mirrors [7][8][9][10] , whereas second one aims at high-power capabilities based on freespace pump coupling and bulk mirrors cavity [4,11,12] . In the last case, up to 154 W power is obtained at ∼1020 nm [12] , but Raman output at this wavelength is not as interesting, because higher power and narrower linewidth are available from YDFLs [13,14] .…”
Section: S a Babinmentioning
confidence: 99%
“…For power scaling, pumping with multimode laser diodes has recently been demonstrated in multimode as well as doubleclad (DC) fibers. 1,2 This approach combines the well-established and well-controlled fabrication, the potentially high resilience to photodarkening, and the high damage threshold of "passive" high-silica fibers (e.g., germanosilicate fibers) with the simplicity of high-power, direct-diode laser pumping, the brightness enhancement enabled by DC fibers, and the advantages of SRS such as wavelength-agility, immunity to high-energy self-Q-switching, and nonlocal gain saturation. 3 However, SRS is a relatively weak process, so high diode brightness and pump intensity are required to reach sufficient Raman gain.…”
Section: Introductionmentioning
confidence: 99%
“…This can be analyzed in terms of a figure of merit (FoM), given by the induced peak Raman gain relative to the background loss, i.e., I P g R ðν peak Þ∕α, where I P is the pump intensity, g R (ν) is the Raman gain coefficient, ν peak is the frequency shift to the Raman gain peak, and α is the fiber background loss, which for simplicity is sometimes assumed to be the same for pump and signal. It was found that a value of the FoM of at least five 1 was needed for efficient conversion in an ideal cavity, whereas a higher value would be required in laser cavities and amplifiers with excess loss or high gain. Today's continuouswave (cw) diode lasers can provide 140 to 200 W of output power at 0.9 to 1 μm from a 105-μm core pigtail at an NA of 0.15.…”
Section: Introductionmentioning
confidence: 99%